Complete intraluminal migration of IPOM mesh causing sub-acute intestinal obstruction: a rare case report - Murugesan, Srinivasan; Amudhan, Anbalagan; Devakumar, Murugesan Satish; Rengasamy, Sudhagar; Thangasamy, Selvaraj; Sathyanesan, Jeswanth (International Surgery Journal, 2022)
Incisional hernia is a common complication following an abdominal surgery. They have ideally managed with open/ laparoscopic mesh repair. Mesh related complication are many due to increasing number of surgeries. This is a case of complete transluminal migration of a IPOM mesh and an eroding Onlay mesh presenting as a sub-acute intestinal obstruction after 2 years of incisional hernia surgery. Mesh migration is one of the complications of incisional hernia repair because of inadequate fixation or by ongoing inflammation (foreign body reaction). Complete trans luminal mesh migration is a rare complication with very few reports noted on bowel and urinary bladder. Transluminal migration into small bowel is a rare complication and it should be considered in differentials whenever patient comes with abdominal symptoms with past history of hernia repair.